Fiscal Responsibility Legislation and Fiscal Adjustment : The Case of Brazilian Local Governments - de Mello, Luiz (World Bank, Washington, DC, 2012)
This paper discusses trends in fiscal adjustment in Brazil since the 1990s, with particular emphasis on the strengthening of institutions for fiscal policymaking, and its effect on local government finances and their ability to invest in infrastructure building and upgrading. Although fiscal adjustment, which is ongoing, has taken a toll on the government's ability to finance much-needed infrastructure investment, it is not the only culprit. A lack of budget flexibility, against a backdrop of increasing downward rigidities in current spending, also constrains the government's ability to invest. The paper argues that regulatory uncertainty in many sectors, particularly water and sanitation, in which the municipalities play a leading role, has discouraged private sector investment and that the financing of infrastructure building and upgrading goes beyond the municipal level of government. Higher-level jurisdictions are responsible for financing investment in energy and transport infrastructure, for example.